Coronavirus 2019-nCoV: A brief perspective from the front line. Issue 4 (April 2020) - Han, Qingmei; Lin, Qingqing; Jin, Shenhe; You, Liangshun
Abstract: A novel coronavirus, designated as 2019-nCoV, hit the central Chinese city of Wuhan in late December 2019, and subsequently spread rapidly to all provinces of China and multiple countries. As of 0:00 am February 9, 2020, a total of 37, 287 cases have been confirmed infection of 2019-nCoV in China mainland, and 302 cases have also been cumulatively reported from 24 countries. According to the latest data, a total of 813 deaths occurred in China mainland, with the mortality reaching approximately 2.2%. At present, there is no vaccine or specific drugs for the human coronavirus. Therefore, it is critical to understand the nature of the virus and its clinical characteristics, in order to respond to the 2019-nCoV outbreak. Thus, the present study briefly but comprehensively summarizes the not much but timely reports on the 2019-nCoV.